Dual and Poly Use of Tobacco Products in a Sample of Pregnant Smokers: A Cross-sectional Study - Bertani, André Luís [UNESP]; Tanni, Suzana Erico [UNESP]; Godoy, Irma [UNESP] (Springer Nature, 2023)
Objectives: Our aim was to assess the use of dual/poly tobacco in a sample of pregnant women. Design: cross-sectional survey. Methods: Twenty prenatal care units in Botucatu, Sao Paulo, Brazil. We evaluated 127 high-risk pregnant smokers during prenatal care. Those who were 12–38 weeks pregnant and were currently smoking conventional cigarettes. The study enrollment took place between January 2015 and December 2015. The dual/poly prevalence of tobacco products during pregnancy and the characteristics related to smoking in pregnant smokers through a specific questionnaire containing questions related to sociodemographic characteristics, comorbidities, gestational history, smoking history, secondhand smoke exposure, nicotine dependence, motivation stage and use of alternative forms of tobacco. Results: Mean age was 26.9 ± 6.6 years, most had only elementary education and belonged to lower income economic groups. Twenty-five (19.7%) smoked conventional cigarettes only while 102 used conventional and alternative forms of tobacco products. Smoking pack-years was significantly lower in those only smoking conventional cigarettes than in dual/poly users. Proportion of patients with elevated degree of nicotine dependence was higher in conventional cigarettes users. On the other side, alcohol intake was higher in dual/poly smokers when compared to conventional cigarettes group. The alternative forms of smoking were associated with significantly higher occurrences of comorbidities as pulmonary, cardiovascular and cancer. Conclusions for Practice: The prevalence of alternative forms users of smoking products is high during pregnancy. These data reinforce the importance of a family approach towards smoking in pregnant women and education about the risks of alternative forms of tobacco.
Keywords: E-cigarette; Pregnancy; Smoking; Tobacco; Waterpipe